Adult frequent presentation to emergency departments and adverse childhood experiences: a scoping review. (December 2021) - Binnie, Vicki; Le Brocque, Robyne; Jessup, Melanie; Johnston, Amy N.B.
Abstract: Background: Extensive literature reports the influence of childhood adversity on adult health, however few studies have explored these life antecedents in people who frequently present to the emergency department. This review synthesizes literature exploring childhood adversity influences on emergency department presentations, if and how it is identified, and interventions addressing the health care needs of this group. Methods: Eight electronic databases were searched. Arksey and O'Malley's framework guided this review, and a quality appraisal was undertaken. Searches included all published studies until August 2020. Results: Twenty-one articles were included in this review. They revealed that childhood adversity is common among adults who frequently attend the emergency department. It impacts physical and psychological health into adulthood and there is no standardized approach described to documenting childhood adversity, nor any consistent intervention reported by emergency departments to address its sequelae in adulthood. Conclusions: Several studies call for screening, intervention, and education to identify and address impacts of childhood adversity for patients who frequently present to the emergency department. However, reliable high-level studies exploring these topics specific to the emergency department are uncommon. Consequently, definitive interventions to address the healthcare needs of this group is lacking and warrants further research.